Baptist Distinctives and the Old Testament - Routledge, Robin (2025)
It has been suggested that being a Baptist and being an Old Testament scholar follow parallel but unconnected trajectories. This article considers why that may be, and explores the possibility of a baptistic approach to Old Testament studies. It affirms the commitment of Baptists to the authority of both testaments and notes significant Baptist Old Testament scholars. However, it also points to the challenge of giving due weight to the Old Testament. It concludes that the linked notions of ‘further light' and ‘unity in disagreement’, which encourage an openness both to new ways of understanding the text and to one another in conversation together, alongside uncovering and applying theological principles found in the Old Testament, offer a way forward that, while not distinctively baptistic, is rooted in convictions that have long been important to Baptists.
Keywords: theological principles; unity in disagreement; further light; Baptist distinctives; Old Testament